2013
DOI: 10.1002/art.37808
|View full text |Cite
|
Sign up to set email alerts
|

A genetic variant in granzyme B is associated with progression of joint destruction in rheumatoid arthritis

Abstract: Objective. Genetic factors account for an estimated 45-58% of the variance in joint destruction in rheumatoid arthritis (RA). The serine proteinase granzyme B induces target cell apoptosis, and several in vitro studies suggest that granzyme B is involved in apoptosis of chondrocytes. Serum levels of granzyme B are increased in RA and are also associated with radiographic erosions. The aim of this study was to investigate GZMB as a candidate gene accounting for the severity of joint destruction in RA.Methods. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 29 publications
0
15
0
1
Order By: Relevance
“…Knevel et al investigated GZMB as a candidate gene accounting for the severity of joint destruction in RA, and found the SNP rs8192916 located in GZMB was associated with the progression of joint destruction. 28 RA patients carrying risk alleles of Dkk-1 had higher serum levels of functional Dkk-1 and more progressive joint destruction over time. 29 The functional LILRA3 appears to confer a higher risk to disease severity in early RA patients.…”
Section: Genetic Factors Predisposing To Ra Severitymentioning
confidence: 94%
“…Knevel et al investigated GZMB as a candidate gene accounting for the severity of joint destruction in RA, and found the SNP rs8192916 located in GZMB was associated with the progression of joint destruction. 28 RA patients carrying risk alleles of Dkk-1 had higher serum levels of functional Dkk-1 and more progressive joint destruction over time. 29 The functional LILRA3 appears to confer a higher risk to disease severity in early RA patients.…”
Section: Genetic Factors Predisposing To Ra Severitymentioning
confidence: 94%
“…Notably, rs4810485 in CD40 and rs7607479 in SPAG16 were identified as risk factors for radiologic progression only in ACPA-positive RA. Genotypings in the EAC were done with allele-specific kinetic PCR analysis,15 Illumina Golden Gate platform,3 4 16 17 Illumina Immunochip,5 18 Sequenom iPLEX6 and LightSnp (Roche) 19. Quality control of genotyping was performed as described previously 3–6 15–19.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, risk factors for this outcome measure may be used to arrive at individualized treatment strategies (van der Helm-van Mil et al, 2010). It has been shown that genetic variants of IL-15 (Knevel et al 2012), IL4R (Krabben et al, 2013), IL2RA (Knevel et al, 2013a), GZMB (Knevel et al, 2013b), Dkk-1 (de Rooy et al, 2013), MMP-9 (de Rooy et al, 2014), MMP-3 (Knevel et al, 2014a), OPG (Knevel et al, 2014b), PTGER4 (Rodriguez-Rodriguez et al, 2015), TRAF1/C5 as well as the rs2833522 SNP (De Rooy et al, 2013) are associated with RA severity as reflected by radiological damage and joint destruction appeared in RA patients. Moreover, it has been reported that RA patients with the Blimp-1 risk allele show more synovial inflammation than those without this allele (Herenius et al, 2011).…”
Section: Genetic Risk Factorsmentioning
confidence: 99%